2011
DOI: 10.4238/2011.october.31.14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glutathione S-transferase polymorphisms on type-2 diabetes mellitus risk

Abstract: ABSTRACT. Glutathione S-transferase (GST) protects cells against oxidative stress. We evaluated the effect of genetic polymorphisms of the GST gene family on the risk of developing type-2 diabetes mellitus and on glycemic control. We also investigated the effects of smoking combined with these polymorphisms on type-2 diabetes mellitus risk. We enrolled 100 type-2 diabetes mellitus patients and 100 healthy controls matched for age, gender and origin, from the Sinai area of Egypt. Fasting serum glucose, HbA 1c a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 24 publications
8
62
2
2
Order By: Relevance
“…Furthermore, unlike other studies in non-European populations, GSTT1 positive allele in our study was associated with hypertriglyceridemia (31)(32)(33).…”
Section: Discussioncontrasting
confidence: 53%
“…Furthermore, unlike other studies in non-European populations, GSTT1 positive allele in our study was associated with hypertriglyceridemia (31)(32)(33).…”
Section: Discussioncontrasting
confidence: 53%
“…Number of female smokers was very less, so it was not possible to compare the results between both the genders. No significant differences were observed between smokers and non-smokers, alcoholic and non-alcoholic individuals, tobacco chewers and non-chewers, carrying homozygous GSTM1/GSTT1/GSTM1T1 null genotype (p>0.05) ( Anantharaman, 2007;Buch et al, 2002;Nair et al, 1999 South Indians c 1744 485 (27.8)** 242 (13.9) 136 (7.8) Naveen et al, 2004;Samson, 2007;Shehnaz et al, 2011;Sreelekha et al, 2001;Suneetha, 2011;Vettriselvi et al, 2006;Vijayalakshmi et al, 2005 East Indians d 67 18(27.0) 9 (13.0) Sikdar et al, 2005 Central Indians e 282 99 (35.1) 37 (13.0) Devi et al, 2008 North Nair et al, 1999;Singh et al, 2009 Blacks b 3008 960 (31.9) 744 (24.9)* 298 (9.9)* Adams et al, 2003;Benzamin et al, 2011;Coutinho et al, 2010;Dandara et al, 2002;Lavender et al, 2009;Masimirembwa et al, 1998;Millikan et al, 2000;Rossini et al, 2002 Caucasians c 2674 1064/2232 (47.7)* 448/2674 (16.7) 31 (9.3) Amer et al, 2011;Baranova et al, 1997;Chen et al, 1996;D'Alo et al, 2004;Gsur et al, 2001;Kargas et al, 2003;Millikan et al, 2000;Mitrunen et al, 2001;Steinhoff et al, 2000;Welfare et al, 1999 Asians 1). The frequency distribution of GSTM1 and GSTT1 alleles were compared between different states of India and other populations all over the world (Table 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…In an Egyptian study (Amer et al,2011) it has been found that the presence of the allele of valine in the GSTP1 gene in T2DM patients was higher than that found in controls groups, the difference was considered significant when compared to Ile allele. The presence of the heterozygous mutant allele of GSTP1 was found in patient subjects more than in the healthy control .The GSTP1 homozygous mutant allele was not found in T2DM patient and control.…”
Section: Discussionmentioning
confidence: 99%